Insecticide Exposure Triggers a Modulated Expression of ABC Transporter Genes in Larvae of Anopheles gambiae s.s. - Mastrantonio, Valentina (Insects, 2019)
Insecticides remain a main tool for the control of arthropod vectors. The urgency to prevent the insurgence of insecticide resistance and the perspective to find new target sites, for the development of novel molecules, are fuelling the study of the molecular mechanisms involved in insect defence against xenobiotic compounds. In this study, we have investigated if ATP-binding cassette (ABC) transporters, a major component of the defensome machinery, are involved in defence against the insecticide permethrin, in susceptible larvae of the malaria vector Anopheles gambiae sensu stricto. Bioassays were performed with permethrin alone, or in combination with an ABC transporter inhibitor. Then we have investigated the expression profiles of five ABC transporter genes at different time points following permethrin exposure, to assess their expression patterns across time. The inhibition of ABC transporters increased the larval mortality by about 15-fold. Likewise, three genes were up-regulated after exposure to permethrin, showing different patterns of expression across the 48 h. Our results provide the first evidences of ABC transporters involvement in defence against a toxic in larvae of An. gambiae s.s. and show that the gene expression response is modulated across time, being continuous, but stronger at the earliest and latest times after exposure.